Mahmud Yunus's Credibility in Hadith Scholarship: A Study of His Contributions and Impact on Contemporary Hadith Literature - Nurul Afifah; Fikri Haekal Amdar (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
Hadith studies in Indonesia often face methodological and epistemological challenges, particularly regarding the limited availability of local literature that can bridge the gap between classical traditions and modern needs. Amidst this dynamic, Mahmud Yunus emerges as one of the Muslim scholars who made a significant contribution through his works on hadith. This article aims to examine the credibility of Mahmud Yunus in the study of hadith, focusing on his contributions and influence on contemporary hadith literature. This research employs a qualitative approach based on library research, analyzing Yunus’ major works such as Ilmu Musthalah al-Hadith and Akhlak Menurut al-Qur’an dan Hadis Nabi. The findings reveal that Yunus’ credibility is not solely grounded in his mastery of classical methodologies in sanad and matn criticism, but also in the pedagogical and structural dimensions he developed through the Islamic education system. His approach succeeded in presenting hadith in a simple, communicative, and applicable manner for Indonesian society. His works effectively bridged the academic tradition of hadith with the needs of national education, thereby making hadith more accessible to the broader Indonesian public. Furthermore, his influence is evident in the construction of contemporary hadith literature that is more applicable and responsive to the challenges of modern times. This article contributes to the development of hadith epistemology in Indonesia by offering an integrative perspective that connects classical tradition, national education, and contemporary discourse in hadith studies.